Increasing Student Argumentative Speech through Basic Debate Training - Syafiq Yastasir; Herick Afrinursalim; Suswati Hendriani; Arjus Putra; Marjohan Marjohan (Jurnal Masyarakat Religius dan Berwawasan, 2024)
This article aims to show the impact of basic debate training on their ability to perform argumentative speech. This training was conducted at SMAN 3 Batusangkar with 14 participants. The training used the Asian Parliamentary Debate System because it is the most widely used debate system in high school. After the training was conducted four times, it was found that their abilities improved both in terms of the quality of their public speaking, their intelligence in arguing, and their confidence. It is hoped that after this debate training, students will be able to compete well in the world of debate.